Kıbrıs’ta Osmanlı Dönemi Sonrası Sosyal Kimlik Arayışı: Kıbrıs Türk Cemaat-i İslamiyesi / Seeking Social Identity after the Ottoman Period in Cyprus: The Turkish Cypriot Community of Islam - Akgün, Sibel (Journal of History Culture and Art Research, 2018)
Abstract The island of Cyprus, one of the most important centers of the Mediterranean, is inseparable from the Anatolian geography for centuries. The Muslim Turkish people who have lived since the time of the Ottoman Empire in Adada have struggled to preserve and then maintain their post-Ottoman existence first. For this purpose, the Muslim Turkish people in the island have always been in contact with the Anatolian geography and have followed this geography closely. At the same time, these people shaped their identities in the axis of Anatolia and organized and strengthened. This study will analyze the Turkish Cypriot Islamic community, an organization established by Muslim Cypriot Turks after World War I. It is an important organization because it has the word, Turkish, in its name. The aim of the study is to show that this organization plays an important role in the formation of identity and organization of the Cypriot Muslim Turkish people in the framework of the theory of Social Identity. In the theory of social identity, people come together around their individual characteristics as well as their distinctive identities. This new center of affiliation is cognitively or emotionally united around common goals and objectives and appeals to a variety of methods to accomplish them. One of the first of these methods is to establish an organization, especially in the light of the intellectuals. This theory provides a suitable framework for analyzing the Islamic community of the Turkish Cypriot community established in 1924 in Cyprus. For this reason, it is preferred. Data interpretation and analysis in the study are interpreted by explanations and analytical methods on the axis of this theory. Öz Akdeniz’in en önemli merkezlerinden biri olan Kıbrıs adası yüzyıllardan Anadolu coğrafyası ile ayrılmaz bir birliktelik içindedir. Adada Osmanlı İmparatorluğu döneminden beri yaşayan Müslüman Türk halkı Osmanlı yönetimi sonrası varlıklarını öncelikle korumak daha sonra da devam ettirmek için mücadele etmiştir. Bu amaçla adadaki Müslüman Türk halkı öncelikle Anadolu coğrafyası ile hep ilişki içinde olmuş hem de bu coğrafyayı yakından takip etmiştir. Bu halk aynı zamanda kimliklerini Anadolu ekseninde şekillendirerek, örgütlenmiş ve güçlenmeye çalışmıştır. Çalışmada Kıbrıslı Müslüman Türk halkının Birinci Dünya Savaşı sonrası oluşturduğu örgütlerden Kıbrıs Türk Cemaat-i İslamiyesi adında ilk olarak Türk kelimesinin kullanılması açısından önemli bir örgüt olarak ele alınmıştır. Çalışmanın amacı Kıbrıslı Müslüman Türk halkının Sosyal kimlik teorisi çerçevesinde bir araya gelmesi ve örgütlenmesi ile kimlik oluşumunda bu örgütün önemli bir rol oynadığını ortaya koymaktır. Sosyal kimlik teorisinde kişiler bireysel özellikleri yanında ayırt edici kimlikleri etrafında bir araya gelmektedir. Bu yeni aidiyet merkezi etrafında bilişsel veya duygusal olarak ortak hedefler ve amaçlar etrafında birleşmekte ve bunları gerçekleştirmek için çeşitli yöntemlere başvurmaktadır. Bu yöntemlerin en başta gelenlerinden biri özellikle aydınların öncülüğünde örgüt kurmaktır. Bu teori Kıbrıs özelinde 1924 yılında kurulan Kıbrıs Türk Cemaat-i İslamiyesini analiz etmede uygun bir çerçeve oluşturmaktadır. Bu nedenle tercih edilmiştir. Çalışmada veri yorumlaması ve analizi ise bu teori ekseninde betimsel ve analitik yöntemle ele alınarak yorumlanmıştır.